2021
DOI: 10.3390/genes12091439
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Trigger in an Animal Model of Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the leading liver chronic disease featuring hepatic steatosis. Mitochondrial β-oxidation participates in the derangement of lipid metabolism at the basis of NAFLD, and mitochondrial oxidative stress contributes to the onset of the disease. We evaluated the presence and effects of mitochondrial oxidative stress in the liver from rats fed a high-fat plus fructose (HF-F) diet inducing NAFLD. Supplementation with dehydroepiandrosterone (DHEA), a multitarget antioxidant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In the relaxed state, mtDNA is accessible for replication by the minimum mitochondrial replisome, which is formed by the hexameric DNA helicase TWINKLE, the tetrameric mtSSB, and the mtDNA polymerase POLγ [ 59 ]. Our results demonstrated that in the liver of MAFLD rats the significantly reduced expression levels of TFAM correspond to a decreased amount of the mtDNA copy number and an impaired expression of the key enzymes of the mitochondrial replisome machinery, further supporting the role of TFAM in the control of mtDNA levels in response to altered metabolic states [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 52%
“…In the relaxed state, mtDNA is accessible for replication by the minimum mitochondrial replisome, which is formed by the hexameric DNA helicase TWINKLE, the tetrameric mtSSB, and the mtDNA polymerase POLγ [ 59 ]. Our results demonstrated that in the liver of MAFLD rats the significantly reduced expression levels of TFAM correspond to a decreased amount of the mtDNA copy number and an impaired expression of the key enzymes of the mitochondrial replisome machinery, further supporting the role of TFAM in the control of mtDNA levels in response to altered metabolic states [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 52%
“…Further, it was unclear what the severity of the disease was in the included studies (as an invasive test, people who were biopsied might have increased pre-test probability of more severe disease). According to Mendoza et al, advanced brosis may increase hepatic copper concentrations, which was part of the reason why that study excluded patients with high liver tissue copper (19); (6) we were unable to address the competing etiologies of copper de ciency and excess; (7) in the liver tissue studies, there are few controls for comparison, in part because of the invasive biopsy procedure required.…”
Section: Figurementioning
confidence: 99%
“…Serum copper is mainly transported by binding to ceruloplasmin which regulates the distribution and release of copper and later played its biological roles ( 6 ). Copper is an indispensable trace element that serves as a structural and enzymatic cofactor for various antioxidant proteins, including cytochrome c oxidase (COX), superoxide dismutase (SOD), and ceruloplasmin ( 7 ). Excessive or deficient copper can lead to mitochondrial dysfunction or dyslipidemia ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, copper deficiency is closely associated with mitochondrial dysfunction and oxidative stress [10]. Decreased liver cellular copper content causes abnormal mitochondrial enlargement, thereby leading to mitochondrial dysfunction [11]. Copper deficiency in the body also leads to abnormal antioxidant function, thus resulting in an aberrant oxidative stress response.…”
Section: Introductionmentioning
confidence: 99%